Ataturk’s Views on Turkish History and The Turkic World and The Reflection of These Views in the Vocabulary of The Nutuk - Nevzat; Güven Alp (Uluslararası Türk Lehçe Araştırmaları Dergisi)
Atatürk's Speech has the distinction of being one of the fundamental works of Turkey and Turkishness. In addition to being a work that describes the establishment and development of the Republic of Turkey, Speech also contains important information in different areas. It is possible to find news from world politics, sections from Turkish history and various findings from the Turkish world in Nutuk. Nutuk is a multifaceted work in which Turkish consciousness and the concept of the Turk are historically explained and supported. The division and fragmentation of the Turkish world during Ataturk's lifetime is a wellknown fact. Each Turkish people sought to save their own independence and remained helpless in the hands of the imperial powers. In the face of this general view, Atatürk and his close friends intervened in the politics of the Turkic world many times and made some initiatives. The reasons for these attempts and struggles were mentioned by Atatürk in his Speech. The essence of the study is to explain and examine the concepts and terms related to the Turkic world in Speech. Thus, the Great Leader's evaluations on issues such as his dominance and curiosity over the vast borders of the Turks, his competence in the historical processes of the Turks, his relationship with cognate communities, and the position of the Turkic states in world politics will be explained through the Speech.